Superconductivity of Liquids - Liu, Huiying; Yuan, Ying; Liu, Donghao; Xin-Zheng Li; Junren Shi (arXiv:1901.02114 [cond-mat], 2019)
We develop a non-perturbative approach for calculating the superconducting transition temperatures (\$T\_\c\\$) of liquids. The electron-electron scattering amplitude induced by electron-phonon coupling (EPC), from which the effective pairing interaction can be inferred, is related to the fluctuation of the \$T\$-matrix of electron scattering induced by ions. By applying the relation, EPC parameters can be extracted from a path-integral molecular dynamics simulation. For determining \$T\_\c\\$, the linearized Eliashberg equations are re-established in the non-perturbative context. We apply the approach to estimate \$T\_\c\\$ of metallic hydrogen liquids. It indicates that metallic hydrogen liquids in the pressure regime from \$0.5\$ to \$1.5$\backslash$mathrm\$\backslash$,TPa\\$ have \$T\_\c\\$ well above their melting temperatures, therefore are superconducting liquids.
Keywords: Condensed Matter - Superconductivity